Cost‐utility analysis of semaglutide for type 2 diabetes after its addition to the National Medical Insurance System in China. Issue 2 (23rd October 2022) - Hu, Shanshan; Gu, Shengying; Qi, Chendong; Wang, Shuowen; Qian, Fengdan; Shi, Chenyang; Fan, Guorong
Abstract: Introduction: The main research purpose is to compare the long‐term cost‐effectiveness of semaglutide (SEMA) with that of dulaglutide (DULA) for patients with inadequately controlled type 2 diabetes throughout their lifetime. If necessary, the second aim is to investigate a further price cut for SEMA to provide sound advice for government drug price adjustments. Methods: Cost‐utility analysis was performed by the United Kingdom Prospective Diabetes Study Outcomes Model 2 (UKPDS OM2) from the perspective of health care providers in China. Baseline characteristics and clinical efficacy of SEMA and DULA were sourced from the high‐dose comparison in the SUSTAIN‐7 trial. A binary search was used to identify the scope for further reduction in the price of SEMA. The impact of individual parameters was assessed with sensitivity analyses. Results: Main analysis (SEMA vs. DULA) revealed a mean difference in quality‐adjusted life years (QALYs) of 0.04 QALYs and costs of $1132.29. The incremental cost‐utility ratio was $26 957.44/QALY, showing that SEMA was a better option compared with DULA. In sensitivity analyses, the discount rate made the greatest contribution to the incremental cost‐utility ratio. In the binary search, there was still scope to reduce the SEMA cost further by approximately 6.83% to be cost‐effective, taking DULA as a reference. Conclusion: After its addition to the National Medical Insurance System in China, SEMA is expected to be a cost‐effective choice compared with DULA for patients with type 2 diabetes with inadequately controlled from the cost‐utility analysis. However, there is still scope to reduce the annual cost of SEMA further.